Phytic Acid Protects against 6-Hydroxydopamine-Induced Dopaminergic Neuron Apoptosis in Normal and Iron Excess Conditions in a Cell Culture Model - Qi Xu; Anumantha G. Kanthasamy; Manju B. Reddy (Parkinson's Disease)
Iron may play an important role in Parkinson's disease (PD) since it can induce oxidative stress-dependent neurodegeneration. The objective of this study was to determine whether the iron chelator, phytic acid (IP6) can protect against 6-hydroxydopamine- (6-OHDA-) induced apoptosis in immortalized rat mesencephalic dopaminergic cells under normal and iron-excess conditions. Caspase-3 activity was increased about 6-fold after 6-OHDA treatment (compared to control; 𝑃<.001) and 30 μmol/L IP6 pretreatment decreased it by 38% (𝑃<.05). Similarly, a 63% protection (𝑃<.001) against 6-OHDA induced DNA fragmentation was observed with IP6 pretreatment. Under iron-excess condition, a 6-fold increase in caspase-3 activity (𝑃<.001) and a 42% increase in DNA fragmentation (𝑃<.05) with 6-OHDA treatment were decreased by 41% (𝑃<.01) and 27% (𝑃<.05), respectively, with 30 μmol/L IP6. Together, our data suggest that IP6 protects against 6-OHDA-induced cell apoptosis in both normal and iron-excess conditions, and IP6 may offer neuroprotection in PD.